(untitled) (The Peerian Journal, 2024)
This work has clearly revealed that small-scale businesses have suffered many setbacks due to a lack of amenities, poor funding, economies of scale, improper management, illiteracy, and other factors. The source of finance for small businesses is not enough to help them expand as expected. Scale business has an impact on the development of a country through the provision of jobs, revenue generation to the government and a boost to the standard of living. Also, it was realised that government intervention is weak and must be enforced. The research design and procedure for data analysis and test of hypothesis revealed that this study is based on the following: government programs and policies, economic growth and development, job creation and poverty alleviation. From the findings of this research, small-scale businesses have an impact on economic development because they create jobs and alleviate poverty. However, government intervention in small-scale businesses is not encouraging; more policies should be profound and implemented correctly